TINJAUAN YURIDIS TERHADAP ANAK DIBAWAH UMUR YANG BEKERJA SELAMA MASA PANDEMI COVID - 19 DI KOTA SAMARINDA - Dita Purnama Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTThe issue of child labor as a type of labor has long been a problem in the world of education, with the addition of regulations stipulated by the Government regarding the Covid-19 Pandemic which greatly impacted the economy of the child's parents, so that many concerns have arisen with the existence of child labor. In fact, the problem of child labor in Indonesia cannot be addressed by choosing whether or not it is permissible. The reality shows that poor families really need work for their children, both to help their family's economy and to sustain their own lives.The type of research used in this research is juridical empirical research, which is a legal research method that uses the rules of law and searches for data or information directly in the field in the form of interviews with resource persons.Various kinds of factors that cause underage children to work are generally economic factors, then habitual factors, self-will (independent), and psychological factors. and outreach to child laborers.With the conditions at the time of the Covid - 19 pandemic, the Government must increase the skills training for child laborers. Parents must play an active role in educating their children so that their children get their rights as children. Child labor rights according to labor law No. 13 of 2013 is the right to survival, the right to protection, the right to develop.Keywords: Covid -19 pandemic, workers, children